The Feed the Future Zone of Influence in Bangladesh: Changes in Selected Indicators from 2011 Baseline to 2015 Midline - Ahmed, Akhter; Hernandez, Ricardo; Abedin, Zeeshan; Ghostlaw, Julie; Hossain, Nusrat Z.; Quabili, Wahid; Sufian, Farha; Tauseef, Salauddin (2017)
Presentation at BFS/USAID Washington, DC March 17, 2016